Temporary Anchorage Device Misplaced into Infratemporal Space - A Case Report - R Mahesh Kumar; Subham Dutta; Swadhinata Handique; CP Sateesh (Indian Journal of Dental Research, 2024)
Introduction: During orthodontic treatment, temporary anchoring devices (TADs) are used to restrain tooth movement. They are a relatively recent addition to the dental toolkit. Aim: As TADs have limitations, Dr. Eric Lieu of Taiwan developed Infra Zygomatic Crest (IZC) screws which are placed between the maxillary second premolar at the bony crest. Treatment Planning: The goal of this case study is to emphasize the value of anatomy, site selection, and IZC retrieval in the event of an accident. Cone beam computed tomography was used as a diagnostic tool for the precise location of the displaced IZC and immediate surgical retrieval was done under local anesthesia from the infratemporal space to prevent further complications. Take-away Lessons: Orthodontists knowledge of soft tissue and hard tissue anatomy and precise positioning is crucial for successful TAD implantation.